Grave of Karl, his wife Jenny, his grandson Harry and his housekeeper Helena Demuth. Graveyard Highgate, London. Before the erection of the Marx-statue in 1956
Grave of Karl, his wife Jenny, his grandson Harry and his housekeeper Helena Demuth. Graveyard Highgate, London. Before the erection of the Marx-statue in 1956.